Cyanidin and Cyanidin-3-Glucoside Alleviate Peptic Ulcer Disease: Insights from in vitro, and in vivo Studies - Prayoga DK; Aulifa DL; Budiman A; Levita J; Jiranusornkul S (Drug Design, Development and Therapy)
Deshanda Kurniawan Prayoga,1,* Diah Lia Aulifa,2,* Arif Budiman,3,* Jutti Levita,4,* Supat Jiranusornkul5,* 1Doctoral Program in Pharmacy, Faculty of Pharmacy, Padjadjaran University, Sumedang, West Java, Indonesia; 2Department of Pharmaceutical Analysis and Medicinal Chemistry, Faculty of Pharmacy, Padjadjaran University, Sumedang, Indonesia; 3Department of Pharmaceutics and Pharmaceutical Technology, Faculty of Pharmacy, Padjadjaran University, Sumedang, Indonesia; 4Department of Pharmacology and Clinical Pharmacy, Faculty of Pharmacy, Padjadjaran University, Sumedang, Indonesia; 5Department of Pharmaceutical Science, Faculty of Pharmacy, Chiang Mai University, Chiang Mai, Thailand*These authors contributed equally to this workCorrespondence: Jutti Levita, Department of Pharmacology and Clinical Pharmacy, Faculty of Pharmacy, Padjadjaran University, Sumedang, West Java, 46363, Indonesia, Tel +6222 84288888 Ext 3510, Email jutti.levita@unpad.ac.idAbstract: Peptic ulcer disease (PUD) remains a significant global health issue, affecting millions despite a decrease in overall prevalence. However, complications continue to persist, with substantial mortality rates in regions like India and China. Current treatments, though effective, have limitations, driving interest in plant-derived therapy. Anthocyanins, including cyanidin and cyanidin-3-glucoside (C3G), are known for their antioxidant and anti-inflammatory properties. This study aims to explore the potential of cyanidin and C3G in alleviating PUD, focusing on their mechanisms of action and therapeutic efficacy in preclinical studies. Articles were searched in Scopus and PubMed databases and filtered for publication from 2014 to 2024, resulting in 89 articles from Scopus and 11 articles from PubMed. The articles were further screened by title, abstract, and full text, resulting in 6 articles. Cyanidin and C3G were described to be able to alleviate PUD by inhibiting the cytokine pro-inflammatory, reducing inflammation in gastric mucosa, and reducing lipid peroxidation in the gastric mucosa. These compounds have proven effective in managing other health problems, including peptic ulcers, but more in-depth exploration in clinical settings is required to confirm therapeutic potential in humans. It is necessary to validate the therapeutic efficacy and safety in human populations. This review provides an overview of preclinical studies of cyanidin and C3G, such as in vitro and in vivo, focusing on mechanism of action or their effectiveness in alleviating peptic ulcers. Keywords: anthocyanins, anti-inflammatory, antioxidant, gastroprotective, preclinical studies